Description Of Patient Knowledge In Hamparan Perak Health Center Against Disease Diabetes Mellitus - Suryati Sinurat; Mangatas Halomoan Parluhutan Hutagalung; Susiani Tarigan (TOUR HEALTH JOURNAL, 2022)
Background: Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action or both. The number of people with DM in Indonesia is ranked 7th in the world. The main factor causing the increase in the number of people with diabetes mellitus is lifestyle changes including diet. This study aims to describe the knowledge of patients at the Hamparan Perak Health Center on Diabetes Mellitus. The type of research used is descriptive with the approach method used is a cross sectional study. Purpose: To find out the description of patient knowledge at the Hamparan Perak Health Center on Diabetes Mellitus. Results: The level of knowledge of the Hamparan Perak Health Center patients about diabetes mellitus was mostly good knowledge as many as 24 people (40%), moderate knowledge as many as 18 people (30%) and 18 people (30%) less. Discussion and Conclusion: The majority of respondents received information about diabetes mellitus through health workers with a total of 24 respondents and a percentage of 40%. The majority of respondents in this study had a good level of knowledge about Diabetes Mellitus. That is 40% of the total respondents have a good level of knowledge about diabetes mellitus as many as 24 respondents. A total of 18 respondents had a moderate level of knowledge of 30%, and those who had less knowledge about diabetes mellitus with a percentage of cases of 30% were 18 people.